Child-rearing experiences, experiential avoidance and depression - Zikopoulou, Olga; Nomikou, Marilia; Simou, Meropi; Simos, Grigoris (Psychology: the Journal of the Hellenic Psychological Society, 2021)
A number of studies has shown that experiential avoidance and psychological inflexibility are associated with emotional difficulties, such as anxiety or depression, and more generally with psychological discomfort. The aim of the present study was to examine the relationship between perceived child-rearing experiences, experiential avoidance and depression in young adults. The sample consisted of 307 participants, women and men, with a mean age of 22,4 years. Greek versions of the Parenting Scale, the Acceptance and Action Questionnaire-ΙΙ, and the DASS-21-Depression scale were utilised to evaluate child-rearing experiences, the degree of experiential avoidance and psychological inflexibility, and symptoms of depression, respectively. All three parameters were significantly intercorrelated, with the strongest relationship observed between experiential avoidance and depression. Partial correlation between child-rearing experiences, and symptoms of depression demonstrated that, after controlling experiential avoidance, there were low but statistically significant correlations between the first two variables. The stepwise regression analysis showed that symptoms of depression were predicted by experiential avoidance and secondarily by the overreactivity subscale of the parenting questionnaire. Data are discussed comparatively with recent relevant evidence. Clinical implications of the findings are indicated, along with directions of future developmental research.